Deconstruction of the Main Protagonists in Ausma Zehanat Khan’s The Unquiet Dead - Luthfialdi Nouval; Mira Utami (Muslim English Literature, 2024)
Jacques Derrida coined two Deconstruction concepts: Binary Opposition and Logocentrism used to analyze the protagonist characters: Esa Khattak and his junior, Rachel Getty, in Ausma Zehanat Khan’s The Unquiet Dead (2013). The binary opposition analysis is used to reveal the binary of the character and its opposition. The results of the analysis show that Khattak as the main protagonist has Good Superior and Resolute traits as his dominant binaries; while Rachel Getty’s central binaries are Forthright and Independent. The concept of logocentrism is decentralizing the dominant binary to create a new center by putting it under erasure. Khattak is symbolized as Justice because his main binary represents the characteristics of justice which is associated with real-world, such as courts. Rachel Getty is symbolized as Feminism because the leading binary represents the characteristics of Feminism which is associated with examples of feminist such as Kartini as the independent women. Thus, Kahn’s novel reconstructs the protagonist characters to question our binary perspectives, such as good/bad, justice/injustice, and feminist/masculine.